Sequential Phosphorylation of Smoothened Transduces Graded Hedgehog Signaling - Su, Ying (2011)
The correct interpretation of a gradient of the morphogen Hedgehog (Hh) during development requires phosphorylation of the Hh signaling activator Smoothened (Smo); however, the molecular mechanism by which Smo transduces graded Hh signaling is not well understood. We show that regulation of the phosphorylation status of Smo by distinct phosphatases at specific phosphorylated residues creates differential thresholds of Hh signaling. Phosphorylation of Smo was initiated by adenosine 3′,5′-monophosphate (cAMP)–dependent protein kinase (PKA) and further enhanced by casein kinase I (CKI). We found that protein phosphatase 1 (PP1) directly dephosphorylated PKA-phosphorylated Smo to reduce signaling mediated by intermediate concentrations of Hh, whereas PP2A specifically dephosphorylated PKA-primed, CKI-phosphorylated Smo to restrict signaling by high concentrations of Hh. We also established a functional link between sequentially phosphorylated Smo species and graded Hh activity. Thus, we propose a sequential phosphorylation model in which precise interpretation of morphogen concentration can be achieved upon versatile phosphatase-mediated regulation of the phosphorylation status of an essential activator in developmental signaling.